Pre- and Postnatal Damage to the Retro-Geniculate Visual Pathways Cause Retinal Degeneration Predictive for Visual Function - Lennartsson, Finn; Öhnell, HannaMaria; Jacobson, Lena; Nilsson, Maria (Frontiers in Human Neuroscience, 2021)
To increase the understanding of the relationship between structure and function in individuals with damage to the brain from different stages of maturation of the visual system, we examined 16 teenagers and young adults. We used diffusion-weighted MRI and fibre tractography of the optic radiation (OR) and optical coherence tomography (OCT) of the peripapillary retinal nerve fiber layer (pRNFL) and the ganglion cell layer + inner plexiform layer (GC+IPL) in the macula. Visual field (VF) function was assessed with the Humphrey Field Analyzer (HFA). Injuries to the immature OR were associated with thinning of the pRNFL and GC+IPL, and corresponding VF defects irrespectively of timing of the lesion. However, in cases with bilateral white-matter damage of immaturity (WMDI) we noticed a well preserved central VF despite a very thin GC_IPL. We speculate that this is due to plasticity in the immature visual system. Similar results were not noticed among cases with unilateral damage, acquired pre- or postnatally, in which the central VF was affected in most cases. OCT has proved to be a valuable targeted tool in children with damage to the retro-geniculate visual pathways, and that focal thinning of the GC+IPL predicts VF defects. This brief research report includes a review of four previously published papers. In addition, we present one new case and apply a recently developed classification system for CVI. The classification was applied on cases with bilateral WMDI to investigate its relation to retinal structure.